Panayiotis Panayides and Ine Jacobs (eds) Cyprus in the Long Late Antiquity: History and Archaeology Between the Sixth and the Eighth Centuries. - Winther-Jacobsen , Kristina (Journal of Greek Archaeology, 2024)
The 17 chapters in this volume are organised into five sections: Introduction (two chapters), Cyprus in between Empires (five chapters), Urban and Rural Perspectives (five chapters), Production and Objects in Use (four chapters) and one concluding chapter.